Feline lower urinary tract disease in a German cat population - Dorsch, R.; Remer, C.; Sauter-Louis, C.; Hartmann, K. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: To investigate epidemiologic data, clinical signs, results of urinalysis and causes of lower urinary tract disease in a German veterinary hospital population of cats and to determine if the demographic data, history, clinical signs and urinalysis results correlate with a particular etiology. Materials and methods: Cats presented with signs of feline lower urinary tract disease (FLUTD) with a documented history and physical examination, a complete urinalysis (urine specific gravity, urine dipstick and sediment, urine culture) of urine obtained by cystocentesis or catheterization, and diagnostic imaging of the urinary tract were included into the study. Cats that had received a previous treatment during the same episode of FLUTD were excluded. Results: A total of 302 cats were included into the study. Cats with FLUTD presented throughout the seasons with similar frequency. The most common diagnosis was feline idiopathic cystitis (FIC) (55.0%), followed by bacterial urinary tract infection (UTI) (18.9%), urethral plug (10.3%) and urolithiasis (7.0%). Urethral obstruction was significantly more frequent in cats with FIC than in cats with UTI. Cats with FIC and urethral plugs were significantly younger and had significantly higher body weights than cats with UTI and neoplasia. FIC and urethral plugs were significantly more common causes of FLUTD in cats younger than 10 years compared to cats that were 10 years or older (65.2% versus [vs.] 35.8% and 13.3% vs. 3.0%), while the incidences of UTI and neoplasia increased with age (12.9% vs. 41.8% and 1.0% vs. 13.4%). Conclusion and clinical relevance: FIC and UTI are the most common diagnoses in cats with FLUTD, with a significant age-related difference in incidence.
Keywords: Bacterial cystitis; urethral obstruction; feline idiopathic cystitis; FLUTD